The Effectiveness of a Training Program Based on Habits of Mind According to Costa's Theory in Developing Achievement Motivation and Self-efficacy among High School Students in Saudi Arabia - Masirah Thani Al-Ruwaili (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims to identify the effectiveness of a training program based on habits of mind according to Costa's theory in developing achievement motivation and self-efficacy among high school students in Saudi Arabia. The study sample was selected from the first-grade secondary school students in Arar, Saudi Arabia, during the first semester of the 2019/2020 academic year. The researcher identified government secondary schools that include two divisions for the first secondary class and chose a school from them. Ond of the two classes was determined randomly to be an experimental group including (24) students, and the other division was determined to be a control group including (26) students. To achieve the aims of the study, a measure of motivation for achievement of high school students, and a measure of self-efficacy, were built. The results showed the following. The training program based on habits of mind according to Costa's theory has been effective in developing achievement motivation and self-efficacy among high school students in Saudi Arabia, as the level of motivation for achievement and self-efficacy among the experimental group students was higher than that of the control group.